Fast and conspicuous? Quantifying salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Advances in Cognitive Psychology)
Particular differences between an object and its surrounding cause salience, guide attention, and improve performance in various tasks. While much research has been dedicated to identifying which feature dimensions contribute to salience, much less regard has been paid to the quantitative strength of the salience caused by feature differences. Only a few studies systematically related salience effects to a common salience measure, and they are partly outdated in the light of new findings on the time course of salience effects. We propose Bundesen’s Theory of Visual Attention (TV A) as a theoretical basis for measuring salience and introduce an empirical and modeling approach to link this theory to data retrieved from temporal-order judgments. With this procedure, TV A becomes applicable to a broad range of salience-related stimulus material. Three experiments with orientation pop-out displays demonstrate the feasibility of the method. A 4th experiment substantiates its applicability t
Keywords: salience; visual attention; Bayesian inference; theory of visual attention; computational modeling; Visual Attention; Computational Modeling; Inference; Judgment; Statistical Probability

Peripheral visual cues: Their fate in processing and effects on attention and temporal-order perception. - Tünnermann, Jan; Scharlau, Ingrid (Frontiers in Psychology)
Peripheral visual cues lead to large shifts in psychometric distributions of temporal-order judgments. In one view, such shifts are attributed to attention speeding up processing of the cued stimulus, so-called prior entry. However, sometimes these shifts are so large that it is unlikely that they are caused by attention alone. Here we tested the prevalent alternative explanation that the cue is sometimes confused with the target on a perceptual level, bolstering the shift of the psychometric function. We applied a novel model of cued temporal-order judgments, derived from Bundesen’s Theory of Visual Attention.We found that cue–target confusions indeed contribute to shifting psychometric functions. However, cue-induced changes in the processing rates of the target stimuli play an important role, too. At smaller cueing intervals, the cue increased the processing speed of the target. At larger intervals, inhibition of return was predominant. Earlier studies of cued TOJs were insensitive
Keywords: cueing; temporal-order judgements; theory of visual attention (TVA); peripheral cue; processing speed; stimulus encoding; prior entry; Attention; Cues; Face Perception; Judgment

Writer’s overload: A multifaceted concept and its clarification. - Scharlau, Ingrid; Karsten, Andrea; Klingsieck, Katrin B. (die hochschullehre)
Many problems student writers are faced with can be understood as writer’s overload, the inability to tackle the high and complex concurrent demands of the writing process. In the present paper, we spell out multiple notions of writer’s overload from the perspectives of cognitive, educational, and sociocultural psychology in order to provide faculty from all disciplines with some background to understand their students’ writing problems. Starting from the Scholarship of Teaching and Learning approach, our aim is to provide teachers with ideas on how they can change crucial aspects of learning activities in their classes and of their teaching practice and study how this affects learning and writing in order to advance the teaching of writing.
Keywords: SoTL; student writing; writer's overload; writing block

(Un)diszipliniertes Schreiben? Schreiben lehren und lernen im Studium und in den Fächern an der Leuphana Universität - Heß, Christiane; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

"Das zu riskieren, ist schon eine große Tat": Ludwig Huber im Gespräch mit Ingrid Scharlau - Huber, Ludwig; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Attention, awareness, discipline, and effort: Die Liberal Arts und ein College in Deutschland - Beck, Karin; Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Die Vergnügungen der anderen: Fachsensible Hochschuldidaktik als neuer Weg zwischen allgemeiner und fachspezifischer Hochschuldidaktik - Scharlau, Ingrid; Keding, Gesche (Pädagogische Hochschulentwicklung: von der Programmatik zur Implementierung)

Sich gar nicht erst im behaglichen Zuhause der eignen Disziplin einrichten: Eine fachfremde Hausarbeit im ersten Semester - Scharlau, Ingrid; Heß, Christiane (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

And now for something completely different - Lehren und Lernen angesichts digitaler Herausforderungen - Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Mathematik schreiben - Scharlau, Ingrid (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2014)